SOME ASPECTS OF THE STRUCTURE OF AMPHIPHILIC MONOLAYERS AT THE AIR-LIQUID INTERFACE DETERMINED BY NEUTRON REFLECTION - Lu, J; Simister, E; Thomas, R; Penfold, J (Publ by Institute of Physics Publishing Ltd, 1994)
Structural information about monolayers of soluble surfactants adsorbed at the air-liquid interface may be determined by neutron reflection in conjunction with isotopic substitution. An outline of the procedure is given and it is shown that there are two types of structural parameter, one determining the thickness σ of the distribution of a given fragment and the other the separation δ between the centres of the distributions of different fragments. The former depends on both the roughness of the layer and the intrinsic thickness of the distribution of the fragment. The δ values are independent of the roughness. The results are summarized for a wide range of surfactants and surface concentrations. It is shown that a simple model of the roughness due to thermal excitations accounts for much of the roughness of the layer, that the hydrocarbon chains are strongly tilted away from the surface normal, and that there is a significant incidence of gauche conformations as the chainlength increases.